Nitrogen and nitric oxide regulate Arabidopsis flowering differently. (July 2019) - Zhang, Zhong-Wei; Fu, Yu-Fan; Zhou, Yang-Hong; Wang, Chang-Quan; Lan, Ting; Chen, Guang-Deng; Zeng, Jian; Chen, Yang-Er; Yuan, Ming; Yuan, Shu; Hu, Jin-Yao
Highlights: Nitrogen and NO regulate plant flowering through different pathways. Both nitrogen and sucrose suppress circadian transcript oscillation. NO treatments increased CRY1, LHY, CCA1 and TOC1, but decreased CO and GI oscillation. Among circadian oscillators, only GI and CO can be S-nitrosylated by NO treatments. Sucrose supplementation counteracted the effects of NO, but not the effects of nitrogen. Abstract: Both nitrogen (N) and nitric oxide (NO) postpone plant flowering. However, we still don't know whether N and NO trigger the same signaling pathways leading to flowering delay. Our previous study found that ferredoxin NADP + oxidoreductase (FNR1) and the blue-light receptor cryptochrome 1 (CRY1) are involved in nitrogen-regulated flowering-time control. However, NO-induced late-flowering does not require FNR1 or CRY1. Sucrose supply counteracts the flowering delay induced by NO. However high-N-induced late-flowering could not be reversed by 5% sucrose supplementation. The high nitrogen condition decreased the amplitudes of all transcripts of the circadian clock. While NO increased the amplitudes of circadian transcripts of CRY1, LHY ( LATE ELONGATED HYPOCOTYL ), CCA1 ( CIRCADIAN CLOCK ASSOCIATED 1 ) and TOC1 ( TIMING OF CAB EXPRESSION 1 ), but decreased the amplitudes of circadian transcripts of CO ( CONSTANS ) and GI ( GIGANTEA ). 5% sucrose supplementation reversed the declines in amplitudes of circadian transcripts of CO and GI after the NO treatment. NO induced S-nitrosation modification on oscillators CO and GI, but not on the other oscillators of the circadian clock. Sucrose supply interestingly reduced S-nitrosation levels of GI and CO proteins. Thus N and NO rely on overlapping but distinct signaling pathways on plant flowering.